Social Media - Eckkrammer, Eva Martha; Steidel, Sandra; Hesselbach, Robert; Zapf, Miriam; Erhart, Pascale; Höfler, Elke; Vesga, Diana; Röhricht, Felix; Eibensteiner, Lukas; Fiedler, Lukas; Meisnitzer, Benjamin; Lachmund, Anne-Marie (Akademische Verlagsgemeinschaft München (AVM), 2025)
This anthology brings together cutting-edge research and insightful analysis from experts in linguistics and foreign language education. Applying different methodological approaches to the analysis of social media, researchers from different fields explore how platforms like Twitter, Instagram, and YouTube are reshaping communication, language learning, and teaching methodologies. From the power of hashtags to the role of influencers, this collection reveals the profound impact of digital interactions on modern linguistics and foreign language education. Essential for educators, researchers, and social media enthusiasts, this book offers a fresh perspective on the evolving landscape of Romance languages (French, Spanish and Portuguese) in the digital age.